Time constant of the cerebral arterial bed in normal subjects - Kasprowicz, Magdalena; Diedler, Jennifer (Ultrasound in medicine & biology, 2012)
The time constant of cerebral arterial bed (in brief time constant) is a product of brain arterial compliance (Ca) and resistance (CVR). We tested the hypothesis that in normal subjects, changes in end-tidal CO2 (EtCO2) affect the value of the time constant. Ca and CVR were estimated using mathematical transformations of arterial pressure (ABP) and transcranial Doppler (TCD) cerebral blood flow velocity waveforms. Responses of the time constant to controlled changes in EtCO2 were compared in 34 young volunteers. Hypercapnia shortened the time constant (0.22 s [0.17, 0.26] vs. 0.16 s [0.13, 0.20]; p = 0.000001), while hypocapnia lengthened the time constant (0.22 s [0.17, 0.26] vs. 0.23 s [0.19, 0.32]; p < 0.0032). The time constant was negatively correlated with changes in EtCO2 (Rpartial = −0.68, p < 0.000001). This was associated with a decrease in CVR when EtCO2 increased (Rpartial = −0.80, p < 0.000001) and Ca remained independent of changes in EtCO2. Ca was negatively correlated with mean ABP (Rpartial = −0.68, p < 0.000001). In summary, the time constant shortens with increasing EtCO2. Its potential role in cerebrovascular investigations needs further studies.